New Tropes for Old: Changing the Conversation in Canadian Writing Centres - Natarajan, Srividya (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
Many of the celebrated and generative tropes that defined the work and self-image of American writing centres—tropes like Stephen North’s “fix-it shop in the basement,” Andrea Lunsford’s “Burkean Parlour,”and Kenneth Bruffee’s “conversation of mankind”—also helped create and affirm an apparent scholarly and pedagogic consensus about writing centre praxis in the Canadian context. I examine the way such tropes imagine our practices—dialogical guidance, collaborative learning, scaffolding, and relationship-building—and the bodies and minds that are enacting them. Using sonnets, narrative, and reflection to propose alternative tropes, I explore how the entry of othered bodies and minds, new perspectives, and marginalized cultures into the writing centre world might change the way we relate to each other and the way we re-imagine our collectivity.